Dis/umanizzare l’arte: Rimbalzando – disforicamente? – sul paradigma dell’autonomia. - Romano Gasparotti (Kaiak)
Let’s try to imagine dysphoric disposition, beyond any clinical-pathological reduction, but leveraging the power, still largely unexplored, contained in the prefix dys considered in its value neither logically negative nor privative. Maybe this experiment would bring with it the possibility of diverting and distracting from that implacable prejudicial and totally absorbing machination, logically undeniable, which less metaphysical philosophy has tried to define onto-theo-logy (Martin Heidegger), logocentrism(Jacques Derrida), theological-political machine (Roberto Esposito) and, finally, agrilogism (Timothy Morton).However, cogitation so-called artistic, considered in its non-symbolic nature, showed and shows to be so much less conditioned by this Machine, which responds to an uncontradictory logic that is binary immune and exclusionary. What Georg W. Bertram recently has defined as the «paradigm of the autonomy of art» is the expression of the philosophical normalization of artistic cogitation. It is undeniable. As Bertram's attempt exemplarily demonstrates – according to the critical interpretation developed on these pages– every attempt to go beyond it in actu signato confirms and corroborates it in actu exercito. Defusing the onto-theo-political-epistemological machination, without denying it, and emptying the paradigm of autonomy fully realize the project of «dehumanizing art» prophesied and experimented, in the early 1900s, by Marcel Duchamp. This act, at last, encourages the manifestations of a musical-dancing cogitation by her inescapably self-skediastic movements, that is, tactically improvisational regardless of any strategy.